Which surgical approach is optimal for joint preparation in talonavicular fusion — A cadaver study. Issue 5 (July 2022) - Andrews, Nicholas A.; Patch, David A.; Torrez, Timothy W.; Sutherland, Charles R.; Harrelson, Whitt M.; Pitts, Charles; Agarwal, Abhinav; Shah, Ashish
Abstract: Background: Fusion of the talonavicular joint has proven challenging in literature. The optimal surgical approach for talonavicular arthrodesis is still uncertain. This study compares the amount of physical joint preparation between dorsal and medial approaches to the talonavicular joint. Methods: Twenty fresh frozen cadaver specimens were randomly assigned to receive either a dorsal or medial operative approach to the talonavicular joint. The joint surface was prepared, and the joint was disarticulated. Image analysis, using ImageJ, was performed by two blinded reviewers to assess the joint surface preparation and this was compared by surgical approach. Results: The dorsal approach had a higher median percentage of talar and total talonavicular joint surface area prepared (75% vs. 59% (p = .007) and 82% vs. 70% (p = .005)). Irrespective of approach, the talus was significantly more difficult to prepare than the navicular (62% vs 88% (p = .001)). Conclusion: The dorsal approach provides superior talonavicular joint preparation. The lateral ¼th of the talar head was the most difficult surface to prepare, and surgeons performing double or triple arthrodesis may prepare the lateral talar head from the lateral approach. Level of evidence: Level V.